Study of serum electrolytes and minerals in hypothyroidism - Padhiary, Madhusmita; Mishra, Tapaswini; Mohanty, Rashmi Ranjan; Mishra, Srimannarayan; Kumar Mishra, Sandeep (International Journal of Medical Research and Review, 2016)
Background of the study: Hypothyroidism is known to affect electrolyte, fat, protein and carbohydrate metabolism. Though the effects of thyroid hormones on lipid profile has been well established, the effects on electrolytes and certain minerals like calcium, magnesium and phosphorus is not clear and the underlying mechanisms responsible for these changes are not well understood. Aim and objectives: The objective was to find out the effects of hypothyroidism on certain electrolytes and minerals levels. Materials and methods: The study was carried out in Dept. of Physiology in collaboration with Medicine, Endocrinology and Biochemistry.100 cases of overt hypothyroidism of both genders aged 25-60 years were chosen,100 age and sex matched healthy controls were chosen. Blood samples were collected from them and serum TSH, total T3, T4, sodium, potassium, calcium, magnesium and phosphorus levels were measured. The values of the above parameters of cases and controls were compared and statistical analysis was made. Results: It was found that the levels of serum sodium, potassium and calcium were significantly decreased in cases than the controls. Serum magnesium and phosphorus were significantly elevated in cases than controls. Conclusion: From this study we were able to conclude that higher the TSH levels, higher will be serum magnesium and phosphorus in the blood and lower will be serum sodium, potassium and calcium levels.